2020
DOI: 10.3390/ma13184103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Chloride Binding Capacity of Cement-Fly Ash System and Cement-Ground Granulated Blast Furnace Slag System with Diethanol-Isopropanolamine

Abstract: Steel bar corrosion caused by chloride was one of the main forms of concrete deterioration. The promotion of chloride binding capacity of cementitious materials would hinder the chloride transport to the surface of steel bar, thereby alleviating the corrosion and mitigating the deterioration. A comparative study on binding capacity of chloride in cement-fly ash system (C-FA) and cement-ground granulated blast furnace slag system (C-GGBS) with diethanol-isopropanolamine (DEIPA) was investigated in this study. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The lamellar thickness was smaller than 0.2 μm and lamellas were clustered at pores in the solidified samples ( Figure 5 e–h) [ 50 ]. The development of lamellar crystals at pores optimized the pore structure, increased the solid capacity of solidified samples, formed retardation against liquid flowing among pores, and decreased leaching of chloride ions to some extent [ 51 , 52 ]. Moreover, it was conducive to the strength growth of solidified samples [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lamellar thickness was smaller than 0.2 μm and lamellas were clustered at pores in the solidified samples ( Figure 5 e–h) [ 50 ]. The development of lamellar crystals at pores optimized the pore structure, increased the solid capacity of solidified samples, formed retardation against liquid flowing among pores, and decreased leaching of chloride ions to some extent [ 51 , 52 ]. Moreover, it was conducive to the strength growth of solidified samples [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, many researchers are focusing on this topic, and construction and building materials have been considered as the best way to reuse such an enormous amount of industry silicate solid wastes [ 1 ]. For instance, steel slag has been successfully used in pavement engineering [ 2 , 3 , 4 ], fly ash is widely reused as cementitious materials in concrete [ 5 , 6 , 7 ], and waste tire rubber can be reused to improve the rutting resistance of asphalt pavement [ 8 , 9 , 10 ]. Along with these developments, there are still many challenges that should be further discussed.…”
mentioning
confidence: 99%
“…Research indicated that the setting time of cement could be significantly shortened due to the introduction of carbide slag, which can be widely used in special projects where a fast setting is required. Blast furnace slag, a by-product from iron production in blast furnaces, was granulated and reused to enhance the corrosion resistance of steel bar used in cement concrete [ 6 ]. The corrosion resistance of the cement-ground granulated blast furnace slag system and cement-fly ash system was compared by adding NaCl in the paste.…”
mentioning
confidence: 99%